Multiutility sophorolipids as nanoparticle capping agents: synthesis of stable and water dispersible Co nanoparticles - Kasture, Manasi; Singh, Sanjay; Patel, Pitamber; Joy, Pattayil Alias; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (Langmuir, 2007)
Sophorolipids are a class of glycolipids that can be obtained from fatty acids by simply treating them with yeast cells (Candida bombicola, ATCC 22214) and glucose. In this letter, we demonstrate the application of sophorolipids obtained from oleic acid as a capping agent for Co nanoparticles. Upon capping the nanoparticle surface, the sugar moiety of these sophorolipids is exposed to the solvent environment, making the nanoparticles stable and water-redispersible.

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

Investigation of magnetic anisotropy in Co nanoparticles using ferromagnetic resonance technique - Sendilkumar, A.; Kasture, Manasi; Patel, Pitamber; Ramana, Chepuri V.; Bhagavatula L. V. Prasad; Srinath, S. (Journal of Physics: Conference Series, 2010)
Using ferromagnetic resonance (FMR) technique, we have investigated the temperature dependence and angular dependence of line width and resonance magnetic field of Co nanoparticles capped with novel alkane carboxylic acids of varying chain lengths. The magnetic properties such as blocking temperature and anisotropy sensitively depend on the chain length as evidenced by the temperature dependence of line width. These results indicate that the magnetic properties of these samples are critically governed by the interparticle interactions which are decided by the chain length. The presence of anisotropy even up to very high temperature above the blocking temperature observed in these studies confirms the presence of inter-particle magnetic interactions as well as intra-particle exchange interaction between the core and shell regions as evidenced by our earlier ac susceptibility and transverse susceptibility measurements on similar system.